Impact of distance from implant center on mechanical circulatory device patient outcomes. Issue 3 (8th January 2021) - Lushaj, Entela B.; Fiedler, Amy; DeCamp, Malcolm; Park, Chan J.; Dhingra, Ravi; Smith, Jason
Abstract: Objectives: Patients on left ventricular assist device (LVAD) support receive extensive care and education before discharge home. We investigated the impact of patient's residential distance from LVAD implantation center on outcomes and survival. Methods: A total of 214 patients received a LVAD between 2006 and 2018 at our institution. Patient's residential distance from the LVAD implantation center, LVAD complications, hospitalization, and death were recorded. Patients were divided into two groups: patients living less than or equal to 100 miles (Group 1), patients living more than 100 (Group 2). Results: A total of 106 patients were assigned to Group 1 and 108 patients were assigned to Group 2. Destination therapy was intended in 20% of patients in Group 1 and 34% in Group 2 ( p = .023). Mean length of stay was 13 ± 9 days for Group 1 and 21 ± 12 for Group 2 ( p < .001). Major postoperative complications were unplanned readmissions due to infections (9% and 12%), gastrointenstinal bleeding (15% and 14%), cerebrovascular accidents (6% and 7.4%), and acute kidney injury (5% and 2%), respectively for Group 1 and Group 2. There was no difference in major complications (all p > .05) and survival between patients in both groups ( p > .05). Conclusions: Distance from implanting center had no impact on adverse outcomes after LVAD implantation. There was a significant increase in hospital stay for patients who live far from the implanting center, suggesting that distance should not be a contraindication when considering patients for LVAD therapy, but plans should be made for prolonged hospital stay or extended local stay near the hospital for close follow‐up.